Multiple skip incision skin-sparing debridement for perianal necrotizing fasciitis: a retrospective study - Qing Long; Chaochi Yue; Bin He; Jun Li (World Journal of Emergency Surgery)
Abstract Aim Multiple skip incision skin-sparing debridement (MSISSD) is a surgical procedure that excises infected tissue to achieve source control while retaining the infected but viable skin, thus overcoming some limitations of traditional surgical debridement. We aimed to introduce this skin-sparing debridement technique for the treatment of perianal necrotizing fasciitis (PNF) and retrospectively analyze its efficacy and safety. Methods Patients with PNF who received MSISSD between January 2021 and August 2024 were included in this retrospective analysis. We investigated the patient characteristics (sex, age, disease duration, and LRINEC score) and clinical data (comorbid diseases, length of stay in the intensive care unit [ICU LOS], microbiological culture results, number of debridements, length of stay [LOS], wound healing time, treatment outcomes, and follow-up status). Results Twenty-two patients with PNF were enrolled, including 19 males (86%) and three females (14%). The median age, disease duration, and LRINEC score was 59.5 years (range: 26–77), 4.5 days (range: 2–10), and 4 (range: 1–10), respectively, and five cases had a LRINEC score ≥ 6 (23%). Among the 22 patients included, the most common comorbid disease was diabetes, with nine cases (41%). Nine (41%) patients were admitted to the ICU, with a median ICU LOS of 2 days. Of the patients with positive wound cultures (14, 64%), polymicrobial infections were identified in 3 (21%) and monomicrobial infections in 11 (79%). The most commonly isolated microorganisms were Escherichia coli (8, 57%) and Klebsiella pneumoniae (5, 36%). One patient underwent debridement twice, while the remaining patients underwent debridement once. The median LOS was 18 days, and the wound healing time was 61 days. No patient underwent reconstruction surgery. During the median follow-up period of 11 months, one patient developed anal fistula 6 months after surgery and recovered after undergoing anal fistula resection. No patient experienced recurrence of PNF or anal incontinence. Conclusion MSISSD appears to be a promising and effective method for skin protection debridement, which can effectively protect the skin while ensuring adequate drainage, and rarely causing severe anal dysfunction.